2008
DOI: 10.1029/2007ja012749
|View full text |Cite
|
Sign up to set email alerts
|

Global MHD simulation of flux transfer events at the high‐latitude magnetopause observed by the Cluster spacecraft and the SuperDARN radar system

Abstract: [1] A global magnetohydrodynamic numerical simulation is used to study the large-scale structure and formation location of flux transfer events (FTEs) in synergy with in situ spacecraft and ground-based observations. During the main period of interest on the 14 February 2001 from 0930 to 1100 UT the Cluster spacecraft were approaching the Northern Hemisphere high-latitude magnetopause in the postnoon sector on an outbound trajectory. Throughout this period the magnetic field, electron, and ion sensors on board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 142 publications
1
11
0
Order By: Relevance
“…A mixture of magnetosheath and magnetospheric ion and electron populations is often detected within FTEs (Le et al, ). FTEs have been studied using simulations (Daum et al, ; Fedder et al, ; Raeder, ), laboratory experiments (e.g., Egedal et al, ; Fox et al, ; Stenzel & Gekelman, ; Yamada, ), ground measurements (Lockwood, Fazakerley, et al, ; Lockwood, Opgenoorth, et al, ; Wild et al, ), and multispacecraft missions as Cluster (e.g., Fear et al, ; Hasegawa et al, ; Roux et al, ; Sönnerup et al, ), Time History of Events and Macroscale Interactions during Substorms (Fear et al, ; Silveira et al, ), and now MMS (Farrugia et al, ; Hwang et al, ). FTE models can essentially be classified into three types of models: elbow‐shaped flux rope model (Russell & Elphic, ), multiple X‐line model (Lee & Fu, ), and single X‐line model (Fear et al, ; Scholer, ; Southwood et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of magnetosheath and magnetospheric ion and electron populations is often detected within FTEs (Le et al, ). FTEs have been studied using simulations (Daum et al, ; Fedder et al, ; Raeder, ), laboratory experiments (e.g., Egedal et al, ; Fox et al, ; Stenzel & Gekelman, ; Yamada, ), ground measurements (Lockwood, Fazakerley, et al, ; Lockwood, Opgenoorth, et al, ; Wild et al, ), and multispacecraft missions as Cluster (e.g., Fear et al, ; Hasegawa et al, ; Roux et al, ; Sönnerup et al, ), Time History of Events and Macroscale Interactions during Substorms (Fear et al, ; Silveira et al, ), and now MMS (Farrugia et al, ; Hwang et al, ). FTE models can essentially be classified into three types of models: elbow‐shaped flux rope model (Russell & Elphic, ), multiple X‐line model (Lee & Fu, ), and single X‐line model (Fear et al, ; Scholer, ; Southwood et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Daum et al. (2008), reinvestigating the conjunction (discussed above) analyzed by Wild et al. (2001, 2003), took the qualitative comparison of Q.‐H.…”
Section: Dayside Processesmentioning
confidence: 99%
“…Several studies (Daum et al, 2008;Q.-H. Zhang et al, 2008Q.-H. Zhang et al, , 2010 have sought to compare the propagation of reconnected flux tubes as observed simultaneously at the magnetopause (in the form of FTE signatures observed by Cluster) and in the ionosphere (as PIFs/PMAFs observed by optical instrumentation or radars). Q.-H. Zhang et al (2008) found qualitative agreement between the northward and dawnward motion of the FTEs observed by Cluster (consistent with the motion predicted by the Cooling et al (2001) model) and the northward and westward flow observed by SuperDARN at the conjugate point in the northern hemisphere ionosphere.…”
Section: Magnetopause Reconnectionmentioning
confidence: 99%
“…The FTE was moving at a fraction of the magnetosheath flow and producing a traveling magnetopause erosion region in its wake. Daum et al [2008] modeled an FTE event observed by ground‐based SuperDARN radars and Cluster using MHD simulation combined with a model of flux tube motion (cooling). They could estimate the spatial and temporal evolution of the FTE.…”
Section: Coordinated Studies Of Magnetospheric Dynamic Processesmentioning
confidence: 99%